Back‐Arc Tectonics and Plate Reconstruction of the Philippine Sea‐South China Sea Region Since the Eocene. Issue 5 (1st March 2023) - Liu, Jinping; Li, Sanzhong; Cao, Xianzhi; Dong, Hao; Suo, Yanhui; Jiang, Zhaoxia; Zhou, Jie; Li, Xiyao; Zhang, Ruixin; Liu, Lijun; Foulger, Gillian Rose
Abstract: Insight into the evolution of Philippine Sea‐South China Sea (SCS) plate motions helps reveal the driving mechanisms of the long‐term tectonic complexity in Southeast Asia. Here, based on the integration of the most recent geological and seismic data, we present a new plate reconstruction model for this region characterized by back‐arc extension and subduction since the Eocene. We suggest that the western boundary of the Philippine Sea Plate was a constant sinistral strike‐slip fault at 55–22 Ma with a clockwise self‐rotation. The connection between the SCS and Shikoku Ridges possibly initiates at 30 Ma, when their spreading times overlapped indicating an affinitive origin and magma source. Regional‐scale geodynamic simulations interfaced with our reconstructed plate motion indicate that the seismic high‐velocity body under the SCS is likely to be the leading edge of the Pacific Slab. Plain Language Summary: Since 55 million years ago, East Asia has been going through a complex plate recombination. Several quantitative plate motion models have been published, but there remain several irrationalities, for example, a footwall plate was moving away from the trench. We established a new model for the Philippine Sea‐South China Sea (SCS) region as an improvement. Our model provides a smooth movement of the Philippine Sea Plate (PSP) from the equatorial zone to its present position, with a clockwise rotation. Based on it, we deduce: (a) the western boundary of the PSP was a sinistral strike‐slip fault; (b) the spreading ridges in SCS and Shikoku Basin were connected at 30 Ma; (c) the stagnant slab under the SCS is a part of the subducting Pacific Slab. Key Points: A new plate reconstruction model of Philippine Sea‐South China Sea (SCS) region since 55 Ma by integrating the latest geological geophysical data The western boundary of the Philippine Sea Plate was a constant sinistral strike‐slip fault at 55–22 Ma The geodynamic model indicates the seismic high‐velocity body under the SCS likely to be the leading edge of the Pacific Slab